2019
DOI: 10.21037/qims.2019.06.21
|View full text |Cite
|
Sign up to set email alerts
|

Personalized 3D printed coronary models in coronary stenting

Abstract: Background: 3D printing has shown great promise in cardiovascular disease, with reports mainly focusing on pre-surgical planning and medical education. Research on utilization of 3D printed models in simulating coronary stenting has not been reported. In this study, we presented our experience of placing coronary stents into personalized 3D printed coronary models with the aim of determining stent lumen visibility with images reconstructed with different postprocessing views and algorithms.Methods: A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…3D volume rendering images provide clear views of the stent location in relation to the coronary anatomy as shown in Figure 9. These preliminary reports along with others suggest the potential value of using 3D printed coronary or cardiac models for studying the optimal CT protocols, although further research is needed to validate these findings [59,62,63]. Further to the above-mentioned applications, 3D printed coronary artery models can also be used to simulate blood flow to the coronary arteries with regard to the hemodynamic changes associated with the development of atherosclerosis.…”
Section: D Printing In Coronary Artery Diseasementioning
confidence: 80%
See 2 more Smart Citations
“…3D volume rendering images provide clear views of the stent location in relation to the coronary anatomy as shown in Figure 9. These preliminary reports along with others suggest the potential value of using 3D printed coronary or cardiac models for studying the optimal CT protocols, although further research is needed to validate these findings [59,62,63]. Further to the above-mentioned applications, 3D printed coronary artery models can also be used to simulate blood flow to the coronary arteries with regard to the hemodynamic changes associated with the development of atherosclerosis.…”
Section: D Printing In Coronary Artery Diseasementioning
confidence: 80%
“…An emerging research area of using 3D printed coronary models is to investigate optimal coronary CT scanning protocols for visualization of calcified plaques and coronary lumen in coronary stenting. Some recent studies by Sun and colleagues reported their experience with promising results achieved through use of personalized coronary models [ 59 , 60 , 61 , 62 , 63 ]. High-resolution CT imaging allows for better visualization and assessment of coronary lumen stenosis caused by calcified plaques, thus further validating previous findings about the effect of spatial resolution on diagnostic assessment of calcified coronary plaques [ 60 ].…”
Section: Clinical Applications Of 3d Printing In Cardiovascular DImentioning
confidence: 99%
See 1 more Smart Citation
“…4, n. 1, p. 38-51 ISSN 2595-1521MARCH 2020 adriana.delmonaco@usp.br will be carried out in the future, such as resistance to fatigue and compression. Biomodels obtained by additive manufacturing, 3D printing, have been shown to be efficient and important in stent implant testing and training (Sun et al, 2019).…”
mentioning
confidence: 99%
“…In that special issue, a number of publications (original studies, technical notes and review articles) were contributed by researchers from different countries with expertise in different fields highlighting the importance of 3D printing in medical applications (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). In addition to these applications, a recent paper in this issue of QIMS presents another new research direction of using personalized 3D printed coronary artery models for simulation of coronary stenting procedure (14).…”
mentioning
confidence: 99%